SARS-CoV-2 Kerala Isolate Spike Protein Induces Cancer Proliferating Markers for Lung and Breast Cancer: An In Silico Approach - Masimani, Vinothini; Ravindrana, Yazhiniv; Venugopal, Gayathriv; Raghavendran, Srikanth; Selvaraj, Stalin; Chandrasekaran, Deepak (Coronaviruses, 2022)
Background: Coronavirus disease (COVID 19) has been emerging as a major threat to humans all over the world. Severe Acute Respiratory Syndrome CoronaVirus 2 (nSARS-CoV-2) is the causative agent for the disease resulting in severe acute respiratory illness. Earlier, it took several years to come up with a vaccine or other sorts of treatments for viral diseases. But now with the advent of biotechnology and development of bio-informatic tools, the process has been accelerated. The WHO reports 39,806,488 affected cases and 1,112,208 deaths till today all over the world (17 Oct 2020). nSARS-CoV-2 has a greater influence on people with comorbidities mainly cancer. Objective: The study herein attempts to understand the binding affinity of the spike protein of the novel coronavirus with the lung and breast cancer marker proteins by docking and ClusPro analysis. Methods: The analysis was conducted in reference to hACE2 (human Angiotensin Converting Enzyme 2), the receptor of nSARS-CoV-2. Total 22 different marker proteins were analyzed using ClusPro. Results: BRCA1 (Breast Cancer type 1 susceptibility protein) and CXCR4 (a chemokine receptor belonging to the G protein coupled receptor family) were found to exhibit higher binding affinities.-73.82 kcal/mol and -66.45 kcal/mol were the global energies they showed upon binding to S protein respectively. Conclusion: Therefore, novel SARS-CoV-2 has a higher chance of inducing cancer in non-cancerous individuals and aids in cancer acceleration in cancer patients . This poses a threat to cancer patients and immunocompromised individuals. The study can be exploited to identify the optimal drug delivery system for novel SARS CoV2.
Keywords: hACE2